Contemporary American women writers : narrative strategies - Rainwater, Catherine, 1953-; Scheick, William J. (The University Press of Kentucky, 2015)
Ann Beattie, Annie Dillard, Maxine Hong Kingston, Toni Morrison, Cynthia Ozick, Grace Paley, Marge Piercy, Anne Redmon, Anne Tyler, and Alice Walker all seem to be especially concerned with narrative management. The ten essays in this book raise new and intriguing questions about the ways these leading women writers appropriate and transform generic norms and ultimately revise literary tradition to make it more inclusive of female experience, vision, and expression. The contributors to this volume discover diverse narrative strategies. Beattie, Dillard, Paley, and Redmon in divergent ways rely.